Clinical Significance and Prognostic Value of CA72-4 Compared with CEA and CA19-9 in Patients with Gastric Cancer. Issue 3 (2000) - Ychou, M.; Duffour, J.; Kramar, A.; Gourgou, S.; Grenier, J.
Abstract : Carcinoembryonic antigen (CEA) and CA 19-9 are both widely used in the follow up of patients with gastrointestinal cancer. More recently another tumor marker, named CA 72-4 has been identified and characterized using two different monoclonal antibodies B72.3 and CC49. Several reports evaluated CA 72-4 as a serum tumor marker for gastric cancer and compared its clinical utility with that of CEA or CA 19-9; few reports concerned its prognostic value. In the present study, CA 72-4 is evaluated and compared with CEA and CA 19-9 in various populations of patients with gastric cancer and benign disease; for 52 patients with gastric adenocarcinoma and 57 patients without neoplastic disease CEA, CA 19-9 and CA 72-4 were evaluated before treatment. Sensitivity of the tumor markers CA 72-4, CA 19-9 and CEA at the recommended cut-off level in all 52 patients were 58%, 50% the sensitivity increased to 75%. of these markers, for non metastatic patients, multivariate analyses indicated that none of the markers were significant, when adjusted for gender and age (which were indicators of poor prognosis); patients with abnormal values of CA72-4 tended to have shorter survival than patients with normal values ( p < 0.07). In the metastatic population, only high values of CA19-9 ( p < 0.02) and gender (women) ( p < 0.03) were indicators of poor prognosis in univariate analysis; multivariate analysis revealed that both CA72-4 ( p = 0.034) and CA19-9 p = 0.009), adjusted for gender were independent prognostic factors. However, CA72-4 lost significance ( p = 0.41) when adjusted for CA19-9 and gender, indicating that CA19-9 provides more prognostic information than CA72-4. When limited to the metastatic male population with normal values of CA 19-9 and CEA, CA 72-4 pretherapeutic positive levels were associated with a worse prognosis ( p < 0.005). In conclusion, this study suggests that the addition of CA 72-4 to CEA and/or CA 19-9 could improve sensitivity in gastric cancer. The prognostic role of this marker is not yet clearly demonstrated but its usefulness in the monitoring of gastric cancer should be taken into account.